NyokJar: Layanan Konsultasi Akademik Digital untuk Mahasiswa Teknologi Informasi - Kurniawan, Dadang; Daniel Tanebeth, Riki; Mudin, Imam; Falgenti, Kursehi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Thesis writing is a crucial component of higher education and a graduation requirement for students. However, many students, particularly those in Information Technology and Information Systems programs, face significant challenges during the thesis process. Common problems include difficulties in selecting research topics, limited understanding of research methodologies, lack of technical skills in system development, and restricted consultation time with academic advisors. In response to these issues, a digital academic consultation platform called NyokJar – Nyok Jalani Skripsi Bareng! was designed and implemented to assist students in completing their theses more efficiently and ethically. This platform was developed using the Waterfall model, which includes the stages of requirement analysis, system design, implementation, testing, and maintenance. The system was built using web technologies such as HTML, CSS, JavaScript, and PHP, and integrated with WhatsApp to enable real-time communication between students and consultants. The system was tested using Black Box Testing, focusing on system functionality from the user's perspective. Test results showed that all major features functioned correctly, and feedback from early users indicated a high level of satisfaction regarding accessibility and ease of use. NyokJar successfully addresses students’ academic and technical needs in thesis completion while upholding academic integrity. With further development, including features such as user login, progress tracking, and digital payment integration, NyokJar has strong potential to evolve into a scalable educational technology (edutech) service that supports academic processes digitally across educational institutions.